Cytoprotective and anti-apoptotic action of HSP70 stress protein in Oreochromis niloticus exposed to residual dilutions of insecticides with fipronil and ethiprole - Guedes, Thays de Andrade [UNESP]; Moreira-de-Sousa, Cristina [UNESP]; Lima, Hellen Maria Soares [UNESP]; Grella, Tatiane Caroline [UNESP]; Socolowski, Priscila Cintra [UNESP]; Fontanetti, Carmem Silvia [UNESP] (Taylor & Francis, 2020)
The objective of this research was to investigate the potential damage caused by the residual concentrations of the insecticides Regent® WS 800 and Curbix® SC 200, containing fipronil and ethiprole, respectively as active ingredients, on the liver of Oreochromis niloticus. The analyses of HSP70 shock protein labelling and cell death process by TUNEL method were performed in order to measure the effects of the exposure of cell repair system of fish to both insecticides. Statistical analyses showed no significant molecular damage to the hepatic tissue of animals. Nevertheless, variations in HSP70 and DNA fragmentation levels, endpoint of cell repair system response and cellular death, respectively, were observed in several groups. These results indicate that the cell repair machinery was efficient when in contact with residual concentrations of insecticides. However, the DNA fragmentation detected by the TUNEL method suggests that even in face of the cytoprotective action of the HSP70 protein, there are damages that become irreparable. To finish, it is worth mentioning that given the results obtained from residual concentrations, use in the field should be with caution.
Keywords: immunostaining; phenylpyrazole; Stress protein; Tilápia; TUNEL